Binder Jetting for Functional Testing of Ceramic Sanitaryware - Cristina Fabuel; María Pilar Gómez-Tena; Arnaldo Moreno; Fernando González-Juárez; Verónica Rico-Pérez; Jordi Balcells (Ceramics)
Additive manufacturing (AM) of ceramics presents a promising approach for the production of complex sanitaryware prototypes, offering advantages in terms of cost and time to market. This study explores binder jetting (BJ) as an optimal AM technique due to its ability to process ceramic materials without thermal stress, accommodate various compositions, and produce large components without support structures. A combination of refractory cement, feldspathic sands, quartz, and calcined alumina was used to formulate 19 different compositions, ensuring adequate green strength and minimizing shrinkage during sintering. A hydration-activated binding method with a water-based binder was employed to enhance part formation and mechanical properties. The results indicate that compositions containing calcined alumina exhibited lower pyroplastic deformation, while optimized gelling agent concentrations improved green strength and dimensional accuracy. The final selected material (SA18) demonstrated high compressive strength, low shrinkage, and a surface roughness comparable to traditional sanitaryware. The application of an engobe layer improved glaze adherence, ensuring a homogeneous surface. This study highlights binder jetting as a viable alternative to traditional ceramic processing, paving the way for its adoption in industrial sanitaryware manufacturing.